ANALISIS KELAYAKAN TERNAK SAPI POTONG KELOMPOK TANI ENGGAL MUKTI PERCUT SEI TUAN SUMATERA UTARA - Tri Ananda Putri; Ira Apriyanti; Gustina Siregar (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2022)
The aims of this research is to find out how much money beef cattle may make in the Enggal Mukti livestock group in Sampali Village, Percut Sei Tuan, North Sumatra. This study employs the case study approach, in which the research is conducted by looking directly at the field, the sampling is done purposefully (deliberately), and the sample method is the probability method. For the data analysis approach utilized to respond to the initial formulation, namely the formulation of variable costs, fixed expenses, and income. Use the calculation Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period to answer the second formulation (PP). The findings of this study show that the enggal mukti beef cattle company earns a lot of money. The income of the enggal mukti beef cattle company is Rp.7.584 million, according to the findings, with an average income of Rp.224.889.882. The Net Present Value (NPV) of the enggal mukti beef cattle business is 3,663,970,800 0, indicating that the enggal mukti beef cattle business is financially feasible to operate, and the IRR value is 40.56 percent, indicating that the use of investment in this business is better and can provide internal profits of 40.56 percent per year. And for the Payback Time (PP) of 1.4, it can be read as a 1.4-year payback period that has met the investment requirement's eligibility criteria.